The Transactions of Buying-Selling of Pre-Baligh Children According to Islamic Law: The Transactions of Buying-Selling of Pre-Baligh Children According to Islamic Law - Zain, Anwar; yusuf, muhammad; faisal, muhammad (Tawazuna, 2022)
Destination study this for know law transaction buying and selling by child who hasn't baligh based on Islamic perspective . Method used  in study this that is study literature with study by laws normative sharia by origin based on the Koran and sunnah then strengthened with ijtihad opinion para cleric fiqh about law transaction jula buy for child prebaligh and must - have attitude conducted by parents  as in charge child . Results research law transaction buy and sell child prebaligh in Islam divided into 3 opinions , namely : 1 ) Yes and legitimate buying and selling child prebaligh with condition already get his parents ' permission . 2) No legitimate buying and selling child prebaligh because the condition of the person who does activity the must Baligh / Mukallaf . 3) Yes and legitimate sell buy buying and selling child prebaligh although no there is permission from his parents but goods / objects purchased including "little " or simple ”. Activity child in buy and sell under not quite enough answer the parents , because the parents who become mukallaf (burdened with reward and sin ) for always knowing in activity child To do purchase in the stalls nor in place purchase where only , so that children miss from impact loss , fraud and fraud by other people or other people affected make a loss on purchases made  child because they no understand score money must  paid